Comprehensive genome analysis of Streptomyces caeruleatus S14 isolated from rice rhizosphere - Mohapatra, Sucharita; Prabhukarthikeyan, S. R.; Biswal, Gayatri; Mishra, Mihira Kumara; Dash, Soumya Shephalika; Nayak, Gyanisha; Keerthana, U.; Parameswaran, C.; Panneerselvam, P.; Mohapatra, S. D. (Frontiers in Plant Science, 2025)
Rice blast, caused by Magnaporthe oryzae, is one of the most devastating diseases affecting rice crops. We investigated effectiveness of Streptomyces spp. against M. oryzae. The results revealed that among the Streptomyces spp., Streptomyces caeruleatus strain S14 demonstrated superior effectiveness in inhibiting the mycelial growth of M. oryzae (74.7%). The strain was identified by sequencing 16S rRNA region. Further, the complete genome sequence of this highly effective strain was acquired using the Illumina NovaSeq 6000 (PE 150), revealing a total genome length of 9,750,804 base pairs (9.7 Mb). The genome comprises 9,191 protein-coding sequences (CDS), 68 transfer RNA (tRNA) genes, 6 ribosomal RNA (rRNA) genes, with an average G+C content of 71.03%. The Streptomyces caeruleatus S14 genome, annotated with RASTtk and genetic code 11, falls under the superkingdom Bacteria. According to annotation statistics from PATRIC, it is a high-quality genome with 97.9% coarse consistency, 93.7% fine consistency, and completeness of 99.9%. The genome included genes related to metabolism, protein processing, defense, virulence, energy, stress response, membrane transport, regulation, cell signaling, cell envelope, DNA processing, cellular activities, RNA processing, and miscellaneous. The complete genome sequence of S. caeruleatus suggests that it offers valuable insights into its antimicrobial activity and provide key genetic traits responsible for pathogen suppression. Incidentally this is the first whole genome sequencing report of S. caeruleatus isolated from rice rhizosphere soil in India.